01.04: Joints between open section beams and tubular columns: New configuration for semi‐rigid and moment resistant bolted joints. (13th September 2017) - Vicente, Guiomar; Simões, Rui; Rebelo, Carlos
ABSTRACT: The appealing shape and the mechanical properties of the tubular members are the main responsible for their growing popularity amongst architects and engineers. However, their potential hasn't been properly explored due difficulties encountered in the joints conception and design, with special emphasis on the bolted joints if rigid and/or full strength behaviour is required for the joint. Currently, in the European regulation scenario, the guidance for the joints design is given in the EN 1993‐1‐8. The recommendations for joints with tubular members are given in its seventh chapter, where only welded solutions are considered. Bolted solutions aren't referred, and no guidance is given to predict the joints rotational stiffness and rotation capacity. However, a window is left open in the standard sixth chapter with the given method to predict the joints structural properties (component method). The method is applicable to joints in frames of any type, independently of its configuration and of the joined members' sections. Once known the nonlinear response of each joint basic component, commonly represented by force‐displacement curves, the component method can be used to predict the joint structural properties. Regarding the current lack of information in this subject, the authors propose a new configuration for joints connecting open section beams to rectangular or square hollow section columns. The configuration was conceived with the double purpose of getting a joint with bending moment resistance capacity and with high initial rotational stiffness. Furthermore, looking on the current regulation scenario, it would be desirable that joints with the proposed configuration could be designed by the component method. Thus, the authors identified the joint active basic components, and are developing experimental work in the sense of establish the force‐displacement curves which represent the nonlinear response of the new basic components. The experimental work, already developed, on the basic components structural response is here summarily presented.